(untitled) (Global Journal of Medical Research, 2020)
Arthroscopic treatment for fractures of the tibial spine is supposed to afford a more accurate approach to the fracture site, decreased morbidity, earlier mobilization, and a shorter hospital stay. We report the accidental lesion of the tibiofibular branch of the popliteal artery during screw fixation of an ACL osseous avulsion using the arthroscopic assisted technique. Until now, there is no report of vascular injury during fixation of the tibial spine using this technique.